Phytochemical Screening of alcoholic extract of Thuja Occidentalis Leaves for Formulation and Evaluation of Wound Healing Ointment - Bharti, Keshav; Sharma, Manmohan; Vyas, Girish Kumar; Sharma, Shailesh (Asian Journal of Pharmaceutical Research and Development, 2022)
Herbal cosmetics are concoctions that are used to beautify and improve the look of humans. The goal of this study was to create and assess a herbal ointment including leaves extract made with alcohol for wound healing. Recent studies in several regions of the world have revealed that t. occidentalis and its active component thujone have a high potential for treating a variety of health problems. T. occidentalis preparations can effectively combat microbial/worm infection. It has antioxidant, anticancer, and anti-inflammatory properties. In addition to these effects, it has insecticidal, molluscicidal, and nematocidal efficacy against certain pests.During the research period, the formulated ointment demonstrated good consistency and spreadability, homogeneity, pH, non-greasy, and no signs of phase separation. Stability characteristics such as visual appearance, nature, viscosity, and aroma of the prepared ointment revealed no significant modification over the research period.